Criminal Responsibility of Legal Persons Introduced by the Special Tribunal for Lebanon - Mareček, Lukáš (Pécs journal of international and European law, 2017)
In the first part of the paper, the author introduces decisions of the Special Tribunal for Lebanon, which, in the end, led to acknowledging the criminal responsibility of legal person for the first time in history of international criminal law. In the second part, the author comments on distinct decision and he considers whether this decision was abrupt and arbitrary or not. Finally, the paper suggests possible implications of the judgement for further development of international criminal law and judiciary.